A parametric study on static behavior and load sharing of multi-bolt hybrid bonded/bolted composite joints. (15th July 2021) - Romanov, Valentin S.; Heidari-Rarani, Mohammad; Lessard, Larry
Abstract: The combination of two joining mechanisms – bonding and bolting – in a single hybrid joint may potentially result in a stronger and more durable joint than either of the separate constituents. Studies have shown that the load sharing between the adhesive and the bolt is a key parameter for such an improvement. The present work executes a parametric study on single-lap hybrid bonded/bolted composite joints with multiple bolts. Joints of five different geometric configurations are subjected to the static tensile loading. The experimental study is supported by modeling results. The study reveals a significant influence of the joint overlap length on the joint strength. The impact of the bolt positioning is less pronounced. Joint stiffness is shown to be mainly governed by the joint overlap length. The load sharing between the adhesive and the bolts is shown to be geometry-dependent, i.e., facilitated by a shorter joint overlap length and smaller bolt-edge distance. The overlap area is shown to be a dominant factor for the strength improvement over that of the load sharing. However, providing that the overlap area is kept unchanged, enhanced load sharing leads to a higher joint strength, revealing their non-linear relationship.